Weapons and Wealth: Economic Effects of the Lucca’s War in Florentine Arms and Armour Production (1429–1433) - Picchianti, Simone (Faces of War, 2025)
In traditional historiography, the wartime context is often judged to have had a uniformly negative impact on medieval economies. While this assessment holds in many respects, it has overlooked the specific sector of arms and armour production and trade, owing to a longstanding lack of focused study. This historiographical gap has thereby distorted our understanding of the period’s economic reality. The present research, grounded in the payment mandates preserved by the Dieci di Balìa, the Florentine war office, during the War of Lucca (1429–1433), seeks to fill that void by offering a concrete appraisal of the arms and armour economy. By examining every recorded expenditure on artillery and firearms with their accompanying gunpowder and bullets, on crossbows and the accessories required for their operation, on polearms, and on defensive armour, the study harnesses the richness and precision of archival evidence to reconstruct quantities purchased, total outlays, production locations and the identities of individual suppliers. Repeated spikes in spending correspond closely with the most intense phases of the campaign, demonstrating that demand for weaponry generated a marked, localised surge in economic activity. Notably, rural hamlets such as Montefioralle and La Trappola emerged as specialised centres for crossbow bolt manufacture, while a Florentine apothecary came to dominate the gunpowder supply. Contrary to the prevailing view that war uniformly depressed Florentine economic life, the conflict with Lucca functioned as a powerful stimulus for sectoral growth, furnishing blacksmiths, carpenters, barrel makers and arms dealers with exceptional earning opportunities. By mapping the supply chains behind every cannon, bolt and spear and by correlating expenditure peaks with the military chronology, this study demonstrates that late-medieval warfare could serve as a positive-sum catalyst, anticipating the organised armaments industries of later centuries and calling for a substantial revision of traditional narratives about the economic impact of war.